DEVELOPING LAMINAR MIXED CONVECTION HEAT TRANSFER THROUGH CONCENTRIC ANNULI (Journal of Engineering, 2010)
Theoretical and experimental study has been conducted on developing laminar mixed convection heat transfer air flow through an annulus for both aiding and opposing flow with uniformly heated inner cylinder and adiabatic outer cylinder for the theoretical part and with uniformly heated inner cylinder while the outer cylinder is subjected to the ambient for the experimental part. In the theoretical investigation the energy equation was first solved using (ADI) method, and then the momentum equations and continuity equation were combined as the pressure correction formula and solved by the SIMPLE algorithm. The present theoretical work covers Ra range from 4.55*10 to 5.649 10° and Re range from 300 to 1000 with radius ratio of 0.555 and Pr-0.72. The velocity and temperature profile results have revealed that the secondary flow created by natural convection have significant effects on the heat transfer process and the results reveal an increase in the Nusselt number values as Ra increases. The experimental setup consists of an annulus which has a radius ratio of 0.555 and inner cylinder with a heated length 1.2m subjected to a constant heat flux while the outer cylinder is subjected to the ambient temperature. The investigation covers Reynolds number range from 154 to 724, heat flux varied from 93 W/m² to 857 W/m², and annulus angles of inclinations a=0° (horizontal), a=20°, 60° (inclined aiding flow), u--20.-60 (inclined opposing flow) and a 90° (vertical). The experimental results show an increase in the local Nusselt number values as the heat flux increases and as the angle of the inclination moves from the positive angles (inclined aiding flow) to the horizontal position and from the negative angles (inclined opposing flow) to the horizontal position. The experimental results show that the local Nusselt number values of the aiding flow are higher than that of the opposing flow at the same Reynolds number and heat flux.